Analisis Kebocoran Heat Exchanger 5 di PPSDM Migas - Rahmanto Widiyantoro (Jurnal Nasional Pengelolaan Energi MigasZoom, 2022)
PPSDM Migas has an oil refinery with a capacity of 600 m3 per day where the crude oil produced will produce various products, such as pertasol CA, pertasol CB, pertasol CC, naphtha, diesel, and residue. One of the operating units used in this production process is a heat exchanger which aims to minimize the use of fuel in the furnace heating process. Of the five heat exchangers in the field, one of the heat exchangers was damaged, namely HE-05. Therefore, an analysis of the causes of damage to HE-05 was carried out with research methods in the form of field studies and literature studies, such as data collection on operating conditions in the Distributed Control System (DCS) and directly in the field using the Piping & Instrumentation Diagram (P&ID) so that it can calculate overall mechanical energy balance. Based on the results of the analysis, it can be concluded that the water content in crude oil exceeds the threshold (< 0.7%) of 5.5%. High water content will affect the steam fraction of crude oil which results in an increase in operating pressure. Then, the safety valve on the stabilizer did not work so that the gasket of the HE-5 was unable to withstand the high pressure in this incident. In addition, inaccurate pressure and temperature sensor readings cause operator delays in dealing with these incidents. Keywords: Crude oil, heat exchanger, water content